New year, new publisher – Nordic occupational health association takes over reins of Scandinavian Journal of Work Environment & Health - O'Donoghue-Lindy, Lisa (Scandinavian Journal of Work, Environment & Health, 2013)
This is a special issue of the Scandinavian Journal of Work, Environment & Health. It is the first issue to be published under a new publisher: the Nordic Association of Occupational Safety and Health (NOROSH). NOROSH is a not-for-profit international society that aims to strengthen Nordic cooperation in the field of occupational safety and health (OSH) by: (i) advancing scientific knowledge and expertise through the publication of original articles, reviews and other information of high interest; (ii) promoting OSH research; and (iii) increasing Nordic and international cooperation in the dissemination of research knowledge. As research is becoming increasingly international, membership in NOROSH is open to all institutes and research organizations worldwide. For the last 35 years, the Finnish Institute of Occupational Health, the National Research Centre for the Working Environment, the Norwegian National Institute of Occupational Health, and – up to 2007 – the Swedish National Institute for Working Life have successfully published the Scand J Work Environ Health. Over that time, the Journal has grown in reputation and its impact factor has risen to a high of 3.122, placing it in the top 16% of the scientific edition of the Public, Environmental and Occupational Health journals in the 2011 Journal Citation Report and the top 6% of the social sciences edition. Submissions to the Journal are at an all time high and the acceptance rate stands at 18% as a result. The number of articles published in each issue will increase over time to incorporate more submissions meeting the Journal’s high quality standards. The Journal is rightly proud of its recent achievements and is recognized for its responsive editorial process and rapid online publication of articles. We believe that NOROSH is a major step propelling the Journal forward on this successful path. The journal is unique among its occupational health competitors in that it retains its publishing independence and is not owned or overseen by any commercial publishing house. As of the end of 2012, the journal had not received outside funding and was sustained mostly through paid subscriptions. We believe the NOROSH platform will enable Scand J Work Environ Health to reach more readers and attract new authors by offering new services and opportunities using internet technologies and moving gradually toward a fully open access (OA) model. In addition to solidifying Nordic cooperation, NOROSH was established in 2012 to secure the economic stability of Scand J Work Environ Health. Due to its not-for-profit status, NOROSH is free to apply for outside funding to supplement income from subscriptions and other sources. This is vital to the future of the Scand J Work Environ Health as we aim to move away from a traditional subscription-based model towards one based on paid international membership of NOROSH and OA article processing charge. Scand J Work Environ Health’s overarching goals moving forward are to increase the relevance and quality of the manuscripts it publishes, speed up response times to authors and decrease publication lags, and most importantly further facilitate accessibility to and heighten awareness of manuscripts that appear in the Journal. The Journal has taken many steps in recent years to achieve these goals, but firmly believes implementing an OA model will prove to be the ultimate solution. Through OA, the Journal and its authors will gain a universal audience for research, increasing its visibility and, as a consequence, having a higher impact on health and safety. University faculties and research bodies can increase awareness about their work and share their knowledge. Readers get free access to literature, which is particularly important for teachers and students faced with access barriers and libraries with their ever-shrinking budgets. Funding agencies and tax payers can see a return on their “investment” as publicly funded research becomes more widely available and disseminated more quickly to be used by others to solve problems related to occupational or environmental health, and drive new technologies and innovations (1). Unlike many large commercial publishers, NOROSH does not believe OA is a threat to quality. The Journal currently has a rigorous peer review process that will continue to be implemented regardless of the OA model. Recent research has shown that OA journals indexed in Web of Science and Scopus share almost the same scientific impact and quality as subscription-based journals. Taking age, discipline, and location of the journal into account, Björk & Solomon (2) found that average citation rates were comparable. In the case of Scand J Work Environ Health, NOROSH believes OA will only serve to enhance citation rates. As a not-for-profit organization, NOROSH’s goal is impact above profit: as long as it is sustainable, OA enables the Journal to fulfil this objective. Scand J Work Environ Health is currently a “hybrid” journal; this means the Journal has “locked” and “unlocked” content. Authors or their supporting network can purchase OA for €1200 per article or some articles are awarded OA status based on merit (eg, Editor’s Pick, highly cited paper). In the last issue of 2012, 50% of the content was OA. While moving in the right direction, the Journal does not believe a hybrid approach is sustainable over the long-term. An increasing number of universities and funding bodies offer grants to cover author processing fees but many of these funds are not available to authors publishing in “hybrid” journals (3). The journals must be 100% OA (“gold” OA) of which there are almost 8400 globally (4). In addition, the number of OA repositories (“green OA”) mandating archiving of papers has soared since 2009 (figure 1). According to the Registry of Open Access Repositories (ROAR), there are 362 approved or proposed institutional or other type of mandates. Included in this figure, are the growing number of funding organizations (such as National Institutes of Health in the US) that require any work paid for by public monies to be freely accessible online to anyone for any purpose, anywhere in the world. This figure also comprises research funded by private foundations such as Wellcome Trust. With its recent announcement that publicly funded scientific research must be immediately and freely available to everyone by 2014, the UK is driving the shake-up of academic publishing in Europe (5, 6). The European Union is likely to follow this example when it announces its Horizon 2020 grants, which will be available for research and innovation projects as of 2014: “European taxpayers have a right to know how their money is invested … information and communication measures will focus on communicating the outcomes of research to policy-makers, companies, innovators and other researchers, including by promoting open access.” (7) The trend is, therefore, moving toward “gold” OA. Nevertheless, despite the urgency around this issue, in order to maintain Scand J Work Environ Health’s rigorous peer review process and cover editing, production, IT, and marketing costs, the Journal cannot become a “gold” OA journal overnight. Our goal is to phase out subscriptions gradually and fund the Journal through individual article processing charges, institutional and individual membership in NOROSH, charging for print copies, and external funding. Like Suber and others (8, 9), we do not feel the article processing charge compromises peer review as many traditional publishers object, but we are concerned that such fees might act as a barrier to authors with limited resources. We therefore hope our institutional stakeholders – many of whom strongly support OA – will see the value in becoming NOROSH members. Depending on the level of membership, NOROSH membership fees cover unlimited free online access to the Scand J Work Environ Health and either full or partial waiver of the article processing charge for first authors from the member institution. For more details, visit http://www.norosh.org/pmwiki.php/Main/Membership. Scand J Work Environ Health will not be a “gold” OA journal in 2013 as some articles will remain “locked” as the first authors choose not to pay the article processing charge and are not affiliated with NOROSH members. With the gradual increase in NOROSH membership, public support, and article processing charges, Scand J Work Environ Health will become a 100% OA journal. At that time, only print copies will require payment and the Journal will be fully available online for free. We recommend authors to encourage their supporting institutions to become NOROSH members in order to influence and support the development of the Journal. Authors who are not members may still publish in the Journal by paying the article processing charge, which can often be reimbursed by funding agencies. We foresee that this fee and NOROSH membership will provide two different financial options that are attractive to all authors. Scand J Work Environ Health highly values its independence and growing reputation. The establishment of NOROSH as the Journal’s new publisher will enable Scand J Work Environ Health to maintain its autonomy. We believe that you, our readers and authors, also value the Journal’s independence and our efforts to make occupational health and safety research as widely available as possible. We hope we can count on your support in this vision. Show your commitment to the Journal’s success by becoming a member of NOROSH today!
Keywords: editorial news; impact factor; NOROSH; open access